Identify the Effects of Ultra Weak Light on Alphacoronavirus and Vero Cells - Hee-Chun Chung; Van Giap Nguyen; Hai-Quynh Do; Mi-Jung Park; Jeong Su Yang; Bong-Kyun Park; Woo-Kyung Jung; Yong Ho Park (International Journal of Coronaviruses, 2021)
Coronavirus is causing many diseases and economic pain to humans and animals. The present study demonstrated how ultra weak lightcause changes in porcine epidemic diarrhea virus (PEDV) and Vero cells. Ultra weak lightactivates Vero cells by lowering pH of maintain media, but have proven no effect of killing the virus.
Keywords: Coronavirus